2021
DOI: 10.1017/cts.2021.534
|View full text |Cite
|
Sign up to set email alerts
|

14820 Mental Health Mobile App Use in Integrated Primary Care Settings: Considerations for Serving Underserved Patients

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Thus far, the absence of timely face-to-face mental health care and current waiting times appear to be relevant context factors for patients to consider DTx for depressive disorders. Also Watanabe-Galloway et al (2021) identified currently underserved patients with depression open-minded towards digital disease-specific interventions ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the absence of timely face-to-face mental health care and current waiting times appear to be relevant context factors for patients to consider DTx for depressive disorders. Also Watanabe-Galloway et al (2021) identified currently underserved patients with depression open-minded towards digital disease-specific interventions ( 52 ).…”
Section: Discussionmentioning
confidence: 99%